The Adult Neck Mass: Predictors of Malignancy. (November 2021) - Kshirsagar, Rijul S.; Anderson, Meredith; Boeckermann, Lauren M.; Gilde, Jason; Shen, Joseph Y.; Meltzer, Charles; Wang, Kevin H.
Objective: Distinguishing benign from malignant adult neck masses can be challenging because data to guide risk assessment are lacking. We examined patients with neck masses from an integrated health system to identify patient and mass factors associated with malignancy. Study Design: Retrospective cohort. Setting: Kaiser Permanente Northern California. Methods: The medical records of adults referred to otolaryngology in 2017 for a neck mass were evaluated. Bivariate and multivariable logistic regression analyses were performed. Results: Malignancy was found in 205 (5.0%) of the cohort's 4103 patients. Patient factors associated with malignancy included sex, age, and race/ethnicity. Males had more than twice the odds of malignancy compared with females (adjusted odds ratio [aOR] = 2.38). Malignancy rates increased with age, ranging from 2.1% for patients younger than 40 years to 8.4% for patients 70 years or older. White non-Hispanic patients had 1.75 times the risk of malignancy compared with patients of other race/ethnicities. The percentage of patients with malignancy increased with increasing minimum mass dimension, from 3.0% in patients with mass size <1 cm to over 31% in patients with mass sizes 2 cm or larger ( P < .0001). Imaging-based mass factors most highly predictive of malignancy included larger minimum mass dimension (≥1.5 cm vs <1.5 cm: aOR = 3.87), multiple masses (2 or more vs 1: aOR = 5.07), and heterogeneous/ill-defined quality (aOR = 2.57). Conclusion: Most neck masses referred to otolaryngology were not malignant. Increasing age, male sex, white non-Hispanic ethnicity, increasing minimum mass dimension, multiple neck masses, or heterogeneous architecture/ill-defined borders were associated with malignancy.